Asas Penghargaan Terhadap Hak Berpendapat Anak: Pengejawantahan ke dalam Pengajaran dan Pembelajaran - Rika Saraswati (Soegijapranata Catholic University, 2018)
The principle of the rights of the child to be heard is one of the principles on the Convention on the Rights of the Child and Indonesia Child Protection Act. The principle is the content of Hukum Perlindungan Anak (Child Protection Law) as a subject on Law curriculum at School of Law, Faculty of Law and Communication, Soegijapranata Catholic University. The implementation of this subject is an academic responsibility in order to transfer new knowledge and values dealing with the rights of the child and to protect children from all of forms of discrimination and violence. The process of transferring knowledge and values has been undertaken by lecturer and students through three main activities, namely teaching, doing research and doing community service